SISTEM INFORMASI BERBASIS WEB MOBILE DATA ELEKTRONIK UMKM PRINGSEWU - Lakasamana Bangsawan; Yuli Cahyo Nugroho; Rinawati Rinawati; Ferry Susanto (LPPM STMIK Pringsewu, 2020)
UMKM is a productive business that is owned by individuals or business entities that have the criteria of micro-businesses. E-UMKM can make it easier to promote UMKM products in the Pringsewu district. So that we to are easily and quickly to find the information about its productions. In this study, the writer tries to design a web mobile-based E-UMKM system using the Waterfall model. The system that is used to describe this model is Entity Relationship Diagram, Context Diagram, Data Flow Diagram, and Flowchart. Behaving E-UMKM in the Pringsewu district, UMKM products will be increasingly recognized by the wider community. It also can increase management activities and increase work motivation so that the E-UMKM in the Pringsewu district can help E-UMKM so that their business is growing.